PTH-338 Postoperative troponin i elevation in patients undergoing major abdominal surgery. (22nd June 2015) - Duff, S; Macdonald, A; Sarma, J; Munoz, S Lavarello
Abstract : Introduction: In the UK, there is an ageing general surgical population with increasing comorbidity. Most studies evaluating postoperative elevation in troponin-I have focussed on surgery in individuals known or suspected to be at high risk of atherosclerotic disease. We aimed to determine the rates of postoperative elevation of troponin-I in patients following elective and emergency major abdominal surgery. Early identification of these patients is vital as this may allow cardiac risk modification improving long-term survival. Method: One hundred patients were recruited. Demographic data was collected. Troponin-I was measured on day one and two postoperatively. If a raised troponin-I level was detected on either blood sample, an electrocardiogram was performed, the patient questioned about the presence of any symptoms and a prompt cardiology consultation was obtained. Results: Fifty-five men and forty-five women were recruited (mean age 70.3, range 45–90). Thirteen of the hundred patients (13%) had postoperatively elevated troponin-I levels on day 1 or 2. Postoperative troponin-I elevation was associated with an increased mean age (P = 0.012) and with increasing CEPOD category of surgery (P = 0.009). No statistically significant difference was seen between groups for P-POSSUM scores of morbidity (P = 0.07) or mortality (P = 0.067). Conclusion: Elevated postoperative troponin-I levels were identified in 13% of general surgical patients undergoing major abdominal surgery. All elevations were asymptomatic and not associated with any cardiological symptoms or ECG abnormality. Elderly patients undergoing emergency surgery are a high-risk group for perioperative cardiac damage which may contribute to the increased morbidity and risk of emergency general surgery. Disclosure of interest: None Declared.